Association of Serum Triacylglycerol (TAG) Level with Urinary Total Protein and Serum Albumin Concentration in Adult Nephrotic Syndrome Patients (Bangladesh Journal of Medical Biochemistry, 2025)
Dyslipidemia is an important secondary biochemical abnormalities in nephrotic syndrome due to proteinuria and hypoalbuminemia. Higher plasma concentration of triacylglycerol (TAG) in nephrotic syndrome is involved in the cardiovascular risk and also accelerates the progression of glomerular dysfunction. This study is designed to evaluate the association between serum TAG level with 24-hour urinary total protein and serum albumin concentration. This analytical type of observational study was carried out in the department of Biochemistry, Dhaka Medical College, Dhaka. A total number of 100 study subjects, age range from 20-50 years, of both gender were selected. Among them 50 (fifty) study subjects were enrolled as diagnosed adult nephrotic syndrome patients from the department of Nephrology, Dhaka Medical College as cases and 50 healthy age and sex matched adult individuals were selected as controls. For baseline information serum TAG level for both cases and controls were measured. Urinary total protein (UTP) and serum albumin level for cases were also measured. Mean values of the variables were compared between cases and controls by unpaired Student’s t test. Categorical variables were analyzed by Chi-square test and correlation between variables were determined by Pearson’s correlation test by using SPSS for windows version 20.0. For all the statistical analyses p